2011
DOI: 10.1260/0958-305x.22.6.695
|View full text |Cite
|
Sign up to set email alerts
|

Fossil Fuel Consumption, Carbon Emissions and Temperature Variation in India

Abstract: Rise in temperature is a cause of major concern across the globe. Through this study an attempt is made to project the corresponding carbon dioxide emissions and temperature variation in India using Auto Regressive Integrated Moving Average Model on past 44 years' data for predicting the future demand of petroleum oil, coal and natural gas in India. It is anticipated that the total demand for petroleum products will double by the year 2020 growing at a rate of 3.5 percent per year. The consumption of coal has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Akkurt et al (2010) compared three time series models including exponential smoothing method, winters prediction model and Box-Jenkins model and the results showed that exponential smoothing model is the most capable tool for prediction (Akkurt et al , 2010). Das et al (2011) with the assistance of the ARIMA model forecasted the demand for petroleum oil, coal and natural gas in India. They also evaluated the amount of carbon dioxide released by the demand for petroleum oil, natural gas and coal by regression method, and found that carbon dioxide emissions could be reduced by replacing the petroleum oil and coal consumption with natural gas (Das et al , 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Akkurt et al (2010) compared three time series models including exponential smoothing method, winters prediction model and Box-Jenkins model and the results showed that exponential smoothing model is the most capable tool for prediction (Akkurt et al , 2010). Das et al (2011) with the assistance of the ARIMA model forecasted the demand for petroleum oil, coal and natural gas in India. They also evaluated the amount of carbon dioxide released by the demand for petroleum oil, natural gas and coal by regression method, and found that carbon dioxide emissions could be reduced by replacing the petroleum oil and coal consumption with natural gas (Das et al , 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through selecting the global time series data in 161 years and applying the linear method and non-linear method to inspect the casual relationship between CO 2 emissions and air temperature, Bai et al [19] proved that CO 2 emissions are the contributor for the climate warming. Das et al's [20] research suggests that the fossil fuel consumption may cause the CO 2 level to rise to one and half times by the year 2020 in comparison to that of the 2008 level, thus causing an increase in the surface temperature by 0.0008 percent per annum. The above stated research studies have obtained comparatively ideal research achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have been done in calculating the effects of a single element of solar technologies like PV panels [14][15][16][17], batteries [18], solar-thermal collectors [19], etc. Some others carried out country-based LCA research [20][21][22][23][24][25][26][27][28] to assess the impacts of solar technologies; they have not considered a global database, which is required for the consistent global practice of LCA [29] and global policy development [23]. Moreover, there are separate LCA analyses to find the hazards of solar technologies that directly affect the human body [30][31][32][33], but they have not measured the rate of energy used from fossil-fuel-based sources in manufacturing solar-PV and solar-thermal systems.…”
Section: Introductionmentioning
confidence: 99%